1992
DOI: 10.1264/microbes1986.7.55
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Microflora in Decayed Picea jezoensis Wood Litter.

Abstract: Seedlings of Picea jezoensis (Yezo spruce) are known to survive well on decayed wood whereas those on the ground are apt to die off due to the attack of plant pathogens. Therefore, microfloral characteristics in the decayed P. jezoensis wood were examined in respect to natural regeneration of the forest. Microbial examination of the decayed wood indicated that Gram-positive but not spore-forming bacteria were dominant. As the decayed wood was strongly acidic, the presence of acidophilic microorganisms was surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The relative abundance of fungi in acid soils is well documented (Alexander 1977), although the publications on the participation of actinomycetes in such a strongly acid environment are rathe,-few. However, recently we have detected several acidophilic actinomycetes in the decayed Picea jezoensis wood litter at pH 3.8 to 4.3 (Nioh et al 1992). Acid-tolerant or acidophilic actinomycetes are likely to share some biochemical pathways in acid tea field soils with fungi.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The relative abundance of fungi in acid soils is well documented (Alexander 1977), although the publications on the participation of actinomycetes in such a strongly acid environment are rathe,-few. However, recently we have detected several acidophilic actinomycetes in the decayed Picea jezoensis wood litter at pH 3.8 to 4.3 (Nioh et al 1992). Acid-tolerant or acidophilic actinomycetes are likely to share some biochemical pathways in acid tea field soils with fungi.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, some kinds of actinomycetes (Khan and Williams 1975;Nioh et al 1992), archaebacteria (Woese and Fox 1977), and nitrifying bacteria (Hankinson and Schmidt 1988) isolated from several acid environments were found to be acidophilic or acid-tolerant.…”
mentioning
confidence: 99%
“…Moreover, Nioh et al (1992) reported that the pH of wood becomes acidic, and wood-inhabiting bacteria become acid-resistant as wood decay progresses in the conifer Picea jezoensis. We found that the different decay stages of Pinus densiflora wood influenced myxomycete community species Fig.…”
Section: Effect Of the Decay State Of Wood On Myxomycete Communitiesmentioning
confidence: 99%
“…In decaying wood, the physical and chemical characteristics of the wood undergo changes over time, and bacteria and nutrient-feeding microbes also change (Ostrofsky and Shingo 1982). Moreover, Nioh et al (1992) reported that the pH of wood becomes acidic, and wood-inhabiting bacteria become acid-resistant as wood decay progresses in the conifer Picea jezoensis. We found that the different decay stages of Pinus densiflora wood influenced myxomycete community species Fig.…”
Section: Effect Of the Decay State Of Wood On Myxomycete Communitiesmentioning
confidence: 99%